Could Obesity be a Triggering Factor for Endometrial Tubal Metaplasia to be a Precancerous Lesion?. (26th March 2020) - El-Saka, Ayman M.; Zamzam, Yomna A.; Zamzam, Yosra A.; El-Dorf, Ayman
Abstract : Background & Aims . Endometrial tubal metaplasia (ETM) is mostly described in conjunction with unopposed estrogen levels, and its association with endometrial hyperplasia and endometrial carcinoma (EC) is striking. Obesity is a risk factor for endometrial hyperplasia and EC development. The aim of this study is to investigate the impact of BMI and serum estradiol level on expression of PAX-2, H-TERT, P16, Ki-67, and P53 in studied ETM in reference to benign endometrium and EC. Methods . The study was conducted on the following groups: group (1) consists of 57 cases that had endometrial biopsies with histologically demonstrable ETM (typical or atypical) and all were subjected to serum estradiol levelling and body mass index (BMI) evaluation; group (2) had adjacent benign endometrial tissue as control; group (3) consists of 52 cases of conventional endometrial carcinoma and 16 serous carcinoma paraffin blocks which were collected and reevaluated. All included groups were immunostained for PAX-2, H-TERT, p16, ki67, and p53. Results . The relation between BMI and serum estradiol level in group 1 and PAX-2, H-TERT, P16, and p53 was statistically significant, while their relation with atypia and ki67 expression was insignificant. Twenty-three ETM cases (40.4%) out of group 1 were all (100%) obese, 87% had high serum estradiol level, and 73.9% were postmenopausal and had a similar immunohistochemical profile as EC cases (group 3). Conclusions . The presence of ETM regardless of the histologic atypia in obese postmenopausal patients with high serum estradiol level is an alarming sign. This implies that ETM might not be as benign as generally accepted, as under certain clinical conditions, it may turn into a potential premalignant lesion.